An appraisal of research in the phonetics and phonology of Thai - Rischel, Jørgen (Annual Report of the Institute of Phonetics University of Copenhagen, 1985)
Since the Second World War there has been a considerable amount of research activity within Thai phonetics and phonology, first by foreign scholars but more recently also by Thai linguists and phoneticians. Thai being a language that plays a central role in connection with such theoretical issues as manner distinctions within stop consonants (VOT, etc.), or inherent pitch and tonogenesis, it was found expedient to take stock of the overall activity in this field. The present paper attempts to combine a survey of the field with some comments on controversial or neglected issues. The emphasis in this presentation is on descriptive and diachronic/comparative studies; work on speech disturbances, language acquisition, or language teaching is mentioned only occasionally.